Thomas the Tank Engine & friends : The best of Percy - Mitton, David; Allcroft, Britt; Carlin, George; Starr, Ringo; Awdry, W.; Britt Allcroft (Firm); Britt Allcroft Productions; Anchor Bay Entertainment, Inc. (Troy, MI : Anchor Bay Entertainment, 2002)
A collection of episodes focusing on the engine Percy.
The ghostly trip -- A scarf for Percy -- Percy takes a plunge -- Percy's predicament -- Thomas, Percy and the mail train -- Percy runs away -- Percy and the signal -- Percy proves a point -- Percy's promise.
Based on the Railway series by Rev. W. Awdry.
Director of photography, Terence Permane ; editor, John L. Wright ; music, Mike O'Donnell, Junior Campbell.
Storytellers, George Carlin, Ringo Starr.
Originally produced for television in 1995-1998.
Not rated.
Children.
Keywords: Thomas the Tank Engine (Fictitious character) -- Juvenile films; Railroads -- Trains -- Juvenile films; Thomas the Tank Engine (Fictitious character) -- Drama; Raildroads -- Trains -- Juvenile drama; Animated television programs; Children's films; Video recordings for the hearing impaired; Television programs